Diversity of termites (Isoptera) on industrial forest plantation of Eucalyptus pellita stands of tropical ecosystem in Riau, Indonesia - SRI RAHAYU PRASTYANINGSIH; Suryo Hardiwinoto; MUSYAFA MUSYAFA; CAHYONO AGUS DWI KORANTO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Prastyaningsih SR, Hardiwinoto S, Musyafa, Koranto CAD. 2020. Diversity of termites (Isoptera) on industrial forest plantation of Eucalyptus pellita stands of tropical ecosystem in Riau, Indonesia. Biodiversitas 21: 5498-5505. Eucalyptus pellita is an alternative tree species for pulp and paper of industrial forest plantation. One of the forest plantation’s negative effect is the loss of biodiversity and vulnerable to pest and disease. Termites are one of the pests attacking the forest plantations and play an important role in the ecological process. Need a better understanding of the termite role ecosystem process in E. pellita stands. This research aimed to determine the diversity of termite species found in E. pellita stands at different rotation and ages of stands. Termite diversity sampled by the transect sampling method in the 4th and 5th rotation with four-level ages (1, 2, 3, 4-years-old). The transect area was divided into 24 plots (100 m x 2 m). The termites in the Eucalyptus stand consist of two families (Termitidae and Rhinotermitidae), five subfamilies (Termitinae, Macrotermitinae, Nasutitermitinae, Rhinotermitinae, and Coptotermitinae), and eight species (Discupiditermes nemorosus, Macrotermes gilvus, Termes rostatus, Amitermes dentatus, Microcerotermes sp., Nasutitermes matangensis, Schedorhinotermes medioobscurus, and Coptotermes havilandi). The diversity index (H) in the 4th rotation was 1.95, while in the 5th rotation was 1.63, with a similarity in the Sorensen Index of 87.71%. The existence of termites is dominated by the wood feeder group. The species richness of the termites at the two rotations increased with the increase of the stand age.. The relative abundance composition of termites in the 5th rotation, is higher than the 4th rotation. Termite occurrence was influenced by necromass, tree biomass, humidity, and temperature.